Analysis of marginal seal of ProRoot MTA, MTA Angelus biodentine, and glass ionomer cement as root-end filling materials: An in vitro study - Sakshi Malhotra; Mithra N Hegde (Wolters Kluwer Medknow Publications, 2015)
Background: Search for a root-end filling material fulfilling all the ideal characteristics is an ongoing process. The present study aimed to evaluate the marginal seal of the following materials when used as root-end filling materials, MTA Angelus, White ProRoot MTA, Biodentine and Glass ionomer cement (GIC). Materials and Methods: Sixty single-rooted maxillary central incisors were included in the study. The crowns were resected followed by cleaning and shaping with hand files and protaper rotary files followed by obturation of the roots. The root ends were resected at 3 mm level. Then, root-end cavity preparation of 3 mm depth was done using ultrasonic tips. The samples were randomly divided into four groups of 15 each and cavities restored with, such as (1) Group 1: MTA Angelus, (2) Group 2: ProRoot MTA, (3) Group 3: Biodentine, and (4) Group 4: GIC. The root samples were coated with two coats of nail varnish and immersed in methylene blue dye 2% for 48 h. Longitudinal root resection was done. The depth of dye penetration was evaluated under the stereomicroscope to examine the extent of microleakage. The amount of dye penetration was measured in millimeters. The results were then statistically analyzed using one-way analysis of variance and post-hoc Tukey's test. Conclusion: Microleakage was present in all the samples. Least amount of apical dye microleakage was seen in biodentine with mean value of 0.16 mm followed by ProRoot MTA 0.68 mm, MTA Angelus 0.74 mm, and GIC 1.53 mm. The best sealing ability was seen in biodentine, and this difference was statistically significant.